3 Tesla (23)Na Magnetic Resonance Imaging During Acute Kidney Injury - Hammon, Matthias; Großmann, Susan; Linz, Peter; Seuss, Hannes; Hammon, Rebecca; Rosenhauer, Daniela; Janka, Rolf Matthias; Luft, Friedrich C.; Titze, Jens; Uder, Michael; Dahlmann, Anke; Cavallaro, Alexander Josef (Academic Radiology, 2017)
Sodium and proton magnetic resonance imaging ((23)Na/(1)H-MRI) have shown that muscle and skin can store Na(+) without water. In chronic renal failure and in heart failure, Na(+) mobilization occurs, but is variable depending on age, dialysis vintage, and other features. Na(+) storage depots have not been studied in patients with acute kidney injury (AKI).We studied 7 patients with AKI (mean age: 51.7 years; range: 25-84) and 14 age-matched and gender-matched healthy controls. All underwent (23)Na/(1)H-MRI at the calf. Patients were studied before and after acute hemodialysis therapy within 5-6 days. The (23)Na-MRI produced grayscale images containing Na(+) phantoms, which served to quantify Na(+) contents. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na(+) levels did not change. Mean Na(+) contents in muscle and skin did not significantly change following four to five cycles of hemodialysis treatment (before therapy: 32.7 ± 6.9 and 44.2 ± 13.5 mmol/L, respectively; after dialysis: 31.7 ± 10.2 and 42.8 ± 11.8 mmol/L, respectively; P > .05). Water content measurements did not differ significantly before and after hemodialysis in muscle and skin (P > .05). Na(+) contents in calf muscle and skin of patients before hemodialysis were significantly higher than in healthy subjects (16.6 ± 2.1 and 17.9 ± 3.2) and remained significantly elevated after hemodialysis.Na(+) in muscle and skin accumulates in patients with AKI and, in contrast to patients receiving chronic hemodialysis and those with acute heart failure, is not mobilized with hemodialysis within 5-6 days.
EVALuna2:14621